Financing political parties in the Algerian system: A comparative study - AGUIS, Mohamed (Journal of Human Sciences, 2020)
Different legislations of modern democratic systems today have acknowledged the need to recognize the role of political parties as a political institution which participates majorly in the foundation and practice of democracy. The legislators have supported political parties , by all means, possible whether through public or private financial funding. The Algerian legislator was no different and followed the path of foreign and Arab democratic systems in supporting the political parties, and different Algerian constitutions are proof of the fact. in addition to the constitution different laws have proved the same thing such as the organic and regulatory laws ;most importantly the law 12-04 law enacted on January 12th.adding to that ,the laws regarding the electoral process most importantly the organic law number 16/10 enacted on August 25th,2016. All of the above illustrations are proof that the legislator is keen to sponsor the political parties which laws, as the funding is legal and under censorship.